2002
DOI: 10.1046/j.0266-4909.2002.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of temporal speech and text cueing in educational multimedia

Abstract: This research focused on the prediction that children in their school setting would learn more from educational multimedia when critical information was presented as spoken instead of textual cues. Analyses of a study (n= 42) showed that 12‐year‐olds did not learn any more from temporal speech cueing than from temporal text cueing. The findings suggest that multimedia learning for children is a different kind of learning experience than for adults or older adolescents. The results indicate underdeveloped execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…As indicated by Mann et al . (2002), individual differences, such as working memory span, can influence the modality effect as well.…”
Section: Individual Differences In the Effect Of Modalitymentioning
confidence: 59%
See 2 more Smart Citations
“…As indicated by Mann et al . (2002), individual differences, such as working memory span, can influence the modality effect as well.…”
Section: Individual Differences In the Effect Of Modalitymentioning
confidence: 59%
“…(2004), this study was user‐paced. Mann et al . (2002) hypothesized that because the working memory processes in these children are not fully developed, there are fewer possibilities for referential connections between the auditory and visual channel.…”
Section: The Modality Effect Tested With Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Jacko [143] studied children's identification of auditory icons and found that as children get older, they improve their ability to identify icons. Mann et al [201] found twelve-year olds did not benefit from listening to important information in multimedia educational software when compared to the same information being presented in text.…”
Section: Use Of Soundmentioning
confidence: 99%
“…The small sample size is homogenous within the context of a primary year group and as such some experimental controls can be applied. Small sample size is common in research on educational multimedia (Mann et al 2002) and in psychological research but there needs to be an evaluation of all possible variable effects.…”
Section: Samplingmentioning
confidence: 99%